Dynamics of the Soil Cover in the Southeast of Europe nd in the Southern Trans-Ural Region during the Subboreal Period - Chendev, Yu.G; Ivanov, I.V (Eurasian soil science, 2007)
An inventory of published data on the natural evolution of forest-steppe, steppe, and semidesert soils in the southern part of the East European Plain and in the southern Trans-Ural region during the Subboreal period of the Holocene has been performed. Schematic maps of the thickness of soil humus profiles and the depth of soil carbonates have been developed for the chronosections of 5000-4200, 4100-3900, and 3800-3200 years ago. On this basis, the areas with specific patterns of natural evolution of soils in the Subboreal period are delineated. DOI: 10.1134/S1064229307110026